Economic Effects of Measures to Adapt to Climate Change in Agriculture - 김창길 (농업부문 기후변화 적응수단의 경제적 효과 분석, 2016)
As further climate change is projected, it will have a substantial impact on the agricultural sector. Frequent abnormal weather and increasing natural disasters in agriculture will affect the best land for cultivating crops. It is thus necessary to establish systematic and phased ways to cope with climate change by introducing a range of approaches in order to minimize the negative impacts on the agricultural sector and to use crises generated by climate change as an opportunity. In reality, it takes long time to establish and implement strategies to cope with climate change, involving huge budget outlays. Therefore, it is essential to analyze the economic effects of the different ways to cope with climate change in order to establish the most effective adaptation scheme. This Report is a result of the Master Project of the Korea Rural Economic Institute on the ‘Analysis of Economic Effects of Adaptation to Climate Change in the Agricultural Sector’. This Report examines adaptation approaches to climate change in the agricultural sector, and then reviews methods of analyzing their economic effects. This is followed by surveying the extent of farmers’ recognition of and adaptation to climate change, and then empirically analyzing the economic effects of adopting a crop insurance scheme and crop switching, and better using weather and climate information. Lastly, this Report suggests the key tasks that are needed, including how to encourage a crop insurance scheme as a means for risk management to build an effective system for coping with climate change on the basis of the survey of farmers’ views and the results of empirical analysis, of crop switching in the face of future climate change, propagation of smart farming to farmers for using convergence technology, systematic training of the workforce, and strengthened education and training. I hope this research will be useful to build a system for coping with climate change in the agricultural sector.